Analisis Faktor-Faktor Yang Mempengaruhi Stress Kerja Pada Karyawan di PT XACTI Indonesia Tahun 2021 - Yulia Anggraeni Hidayat Putri; Ira Sukyati; Alma Putri Febriyanti (Buletin Kesehatan: Publikasi Ilmiah Bidang kesehatan, 2021)
Shift work is a system implemented by the company to increase production optimally and continuously by working 24 hours a day. In addition, to optimize the working power of industrial machines and to increase company profits, this will have a negative impact on employees, causing mental fatigue or stress. Data based on Riskesdas 2018 shows that the prevalence of severe mental disorders in the Indonesian population increased significantly compared to Riskesdas 2013 which rose from 1.7‰ to 7‰ and mental emotional disorders rose from 6% to 9.8% of the total population of Indonesia. This study aims to determine the relationship between work shifts and work stress for employees at PT Xacti Indonesia in 2021. This research is an analytical study using a cross sectional study design. Samples were taken as many as 89 people using purposive sampling technique. Measurement of work stress was measured using a health, safety and executive questionnaire. With the aim of research to find out the factors that most influence work stress, statistical tests were carried out using the Multinominal Logistics Regression test, with the results that the average respondents were mostly women (56.2%), with 1-5 years working period of 82%, and had a high level of moderate work stress by 51.7%. And the variable that has a correlation with work stress is shift work. The work shift is significant in the logit 1 function, which means that low work stress occurs in the morning work shift. The percentage value of the accuracy of all models is 53.9% which means that there are 53.9% (54%) observations can be classified correctly. With this research, it is hoped that the company can manage the work shift system better. If there are employees who have high stress levels, the company must provide input and motivations so that these employees can be more enthusiastic so that their stress levels can decrease.